Transtelephonic Electrocardiographic Transmission in the Preparticipation Screening of Athletes. (24th October 2007) - Samaras, Theodoros; Karavasiliadou, Savvato; Kouidi, Evangelia; Sahalos, John N.; Deligiannis, Asterios
Abstract : Transtelephonic electrocardiographic transmission (TET) is the most widespread form of telecardiology since it enables clinicians to assess patients at a distance. The purpose of this study was to assess the efficacy and effectiveness of TET either by fixed telephone line (POTS) or by mobile phone in the preparticipation screening of young athletes. A total of 506 players, aged 20.5± 6.2 years, from 23 soccer clubs in the prefecture of Thessaloniki, Greece, were physically examined in their playfields by a general practitioner (GP) and had their ECG recorded. In 142 cases, and on the judgment of the GP, the ECG was transmitted via POTS and/or global system for mobile communications (GSM) to a specialised medical centre where it was evaluated by a cardiologist. The mean total time for recording, storing, and transmitting the ECG was four minutes per subject. It was found that the success rate for transmission at first attempt was similar for both fixed and mobile networks, that is, 93% and 91%, respectively. The failure rate in the GSM network was correlated to the reception level at the site of transmission. Only in about half (n = 74) of the transmitted ECGs did the cardiologist confirm "abnormal" findings, although in 16, they were considered to be clinically insignificant. Consequently, 58 athletes were referred for further medical examination. Our results indicate that TET (either by fixed telephone line or by mobile phone) can ensure valid, reliable, and objective measurements, and significantly contribute to the application of medical screening in a great number of athletes. Therefore, it is recommended as an alternative diagnostic tool for the preparticipation screening of athletes living in remote areas.